The quality of sugarcane registered to women: Evidence from an intervention in Uganda - Ambler, Kate; Jones, Kelly M.; O'Sullivan, Michael (International Food Policy Research Institute, 2019)
In smallholder households that engage in commercial agriculture, women are often involved in the phys-ical labor related to the cash crop, but do not engage in the market-facing activities. As a result, men tend to control the profits from these crops, which are increasingly important to household livelihoods. The Farm and Family Balance project implemented an intervention that sought to mitigate this issue. The project encouraged households associated with a large sugar company near Jinja, Uganda to regis-ter at least one of their sugarcane blocks with the wife instead of the husband, thereby including her in the market activities associated with that block and giving her access to the block profits. Take-up of the intervention was high; 72% of households that were offered the opportunity chose to participate. The project was implemented as a randomized control trial to allow for the study of the impacts on house-holds. In this note, we provide information regarding the quality of the blocks transferred to women and the resulting changes to the company’s portfolio.